Interindividual Variability of Functional Connectivity in Awake and Anesthetized Rhesus Macaque Monkeys - Xu, Ting (Biol Psychiatry Cogn Neurosci Neuroimaging, 2019)
BACKGROUND: Nonhuman primate (NHP) models are commonly used to advance our understanding of brain function and organization. However, to date, they have offered few insights into individual differences among NHPs. In large part, this is due to the logistical challenges of NHP research, which limit most studies to 5 subjects or fewer. METHODS: We leveraged the availability of a large-scale open NHP imaging resource to provide an initial examination of individual differences in the functional organization of the NHP brain. Specifically, we selected one awake functional magnetic resonance imaging dataset (Newcastle University: n = 10) and two anesthetized functional magnetic resonance imaging datasets (Oxford University: n = 19; University of California, Davis: n = 19) to examine individual differences in functional connectivity characteristics across the cortex as well as potential state dependencies. RESULTS: We noted significant individual variations of functional connectivity across the macaque cortex. Similar to the findings in humans, during the awake state, the primary sensory and motor cortices showed lower variability than the high-order association regions. This variability pattern was significantly correlated with T1-weighted and T2-weighted mapping and degree of long-distance connectivity, but not short-distance connectivity. The interindividual variability under anesthesia exhibited a very distinct pattern, with lower variability in medial frontal cortex, precuneus, and somatomotor regions and higher variability in the lateral ventral frontal and insular cortices. CONCLUSIONS: This work has implications for our understanding of the evolutionary origins of individual variation in the human brain and methodological implications that must be considered in any pursuit to study individual variation in NHP models.